Missile Guidance and Control Systems - Siouris, George M. (Springer, 2004)
Airborne Vehicle Guidance and Control Systems is a broad and wide- angled engineering and technological area for research, and continues to be important not only in military defense systems but also in industrial process control and in commercial transportation networks such as various Global Positioning Systems (GPS). The book fills a long-standing gap in the literature. The author is retired from the Air Force Institute and received the Air Force's Outstanding Civilian Career Service Award